Active Learning Management to Develop Students into Becoming “Innovators” - Nimkham, Sudaporn (JOURNAL OF SOUTHERN TECHNOLOGY, 2024)
Active learning occurs when learners engage in a learning process through collaborative thinking, doing, and participating in activities. This approach allows students to learn, inspire, develop independent learning skills, discover their own potential, and contribute to the body of knowledge in their fields. All these are the consequences of active learning which gives learners the freedom to carry out real-world experiences based on their own curiosity or passions. It also supports hands-on learning that fosters 21st-century skills. Moreover, through active learning students can turn imagination into creativity, and thus gradually develops them as innovators. This paper aims to present a guideline for active learning to develop learners into "innovators." It explains the current social conditions, desired characteristics of learners in the 21st century, reasons for developing learners to be innovators, characteristics of innovators, as well as approaches to manage active learning in order to turn learners into "innovators."